New Perspectives on Iron Uptake in Eukaryotes - Sherman, Harry G.; Jovanovic, Carolyn; Stolnik, Snow; Baronian, Kim; Downard, Alison J.; Rawson, Frankie J. (Frontiers in Molecular Biosciences, 2018)
All eukaryotic organisms require iron to function. Malfunctions within iron homeostasis have a range of physiological consequences, and can lead to the development of pathological conditions that can result in an excess of non-transferrin bound iron (NTBI). Despite extensive understanding of iron homeostasis, the links between the ‘macroscopic’ transport of iron across biological barriers (cellular membranes) and the chemistry of redox changes that drive these processes still needs elucidating. This review draws conclusions from the current literature, and describes some of the underlying biophysical and biochemical processes that occur in iron homeostasis. By first taking a broad view of iron uptake within the gut and subsequent delivery to tissues, in addition to describing the transferrin and non-transferrin mediated components of these processes, we provide a base of knowledge from which we further explore non-transferrin bound iron uptake. We provide concise up-to-date information of the transplasma electron transport systems (tPMETSs) involved within NTBI uptake, and highlight how these systems are not only involved within NTBI uptake for detoxification but also may play a role within the reduction of metabolic stress through regeneration of intracellular NAD(P)H/NAD(P)+ levels. Furthermore, we illuminate the thermodynamics that governs iron transport, namely the redox potential cascade and electrochemical behaviour of key components of the electron transport systems that facilitate the movement of electrons across the plasma membrane to the extracellular compartment. We also take account of kinetic changes that occur to transport iron into the cell, namely membrane dipole change and their consequent effects within membrane structure that act to facilitate transport of ions.